Ruang Baca Virtual: Inovasi Layanan Pembelajaran di Perpustakaan Universitas Terbuka - M. Pandu Ristiyono (Jurnal Dinamika Pendidikan dan Pembelajaran, 2015)
The Open University is a public university that organizes the system of education through open and distance learning system (PTJJ) with the concept of education for all and lifelong learning promoted by UNESCO. Purpose of the policy makers is how supreme in UT in this case Rector, knowing how important the role of the Library in learning, especially for High Education, the Open and Distance Learning. And also help the students in the corners of the archipelago, which is often constrained in the delivery module for Geographical Factors. The Open University Library to serve as a medium of learning for students through the Virtual Reading Room.